Optimization of Silver Nanoparticles Production by E. coli Bacterium (DH5α) and the Study of Reaction Kinetics - Reza Ghorbani, Hamid; Attar, Hosein; Akbar Safekordi, Ali; Mahdi Rezayat Sorkhabadi, S. (Asian Journal of Chemistry, 2011)
In this research, silver nanoparticles formation by E. coli bacterium (DH5α) is investigated. Effect of silver nitrate concentration, mixing ratio of filtrate of bacterium culture to silver nitrate, temperature and pH on size and production efficiency was studied. In order to identify and analyze nanoparticles, UV-VIS spectroscopy, atomic absorption spectroscopy, transmission electron microscopy and dynamic light scattering were used. It was found that initial concentration of silver nitrate play a key role in formation of nanoparticles. In addition, it was found that in lower temperatures, the size of silver nanoparticles is smaller and their distribution is narrower. Increase of pH causes increase in the size of nanoparticles and their accumulation. Further, the kinetics of Ag nanoparticles formation was studied. It was found that in similar physical conditions, the reaction of naoparticles formation and the reduction of silver ions are faster in the less mixing ratio of filtrate